The most efficient Czech SME sectors: An application of robust data envelopment analysis - Jan Průša (Charles University in Prague, Institute of Economic Studies (IES), 2009)
This paper analyzes the efficiency of Czech small and medium enterprises. We use the data from 2002 to 2005 of thirty manufacturing industries, each divided into five subgroups according to the number of employees. We employ standard and advanced robust data envelopment analysis (DEA) to obtain cross-sectional rankings of individual industries. The results reveal substantial variance in the efficiency scores, which is only partly removed by the robust DEA specification. We found that the majority of firms operate below full efficiency; with only a few companies (industries) belonging to top performers. Average efficiency lies between 50 to 70 per cent of the best sectors. We conclude that only a minor proportion of Czech SME concentrate on high value added production.
Keywords: D24; L60; L70; 330; production; efficiency measurement; data envelopment analysis; small and medium enterprises; KMU; Verarbeitendes Gewerbe; Technische Effizienz; Data-Envelopment-Analyse; Tschechische Republik